Designing an Information System Model for Project-Based Learning Management and E-Showcase Using a Design Thinking Approach - R.R. Ardiyanti Putri Hapsari; Berlian Al Kindhi (IPTEK The Journal of Engineering, 2026)
The Department of Electrical Automation Engineering manages Project-Based Learning (PjBL) through several separate media. This condition makes it difficult for users to browse documents, monitor progress, access assessment rubrics, and publish project results. This study designs an information system model for PjBL and e-Showcase management using a Design Thinking approach. Carrying out the Empathize, Define, Ideate, Prototype, and Test stages. Then, data is collected through observations and interviews with 12 students and 4 lecturers. Processing the findings into 17 initial codes, 10 themes, 10 functional requirements, and 4 non-functional requirements. Determine the impact-effort score through discussions with developers who understand the level of difficulty of each feature. Then, an interactive prototype is created and tested on 19 users, consisting of 12 students, 4 lecturers, and 3 admins. The test resulted in 139 task implementations. Participants completed 131 tasks, or 94.2%, without instructions, and 8 tasks, or 5.8%, with general instructions regarding menu locations. The average task ease of use was 4.38 out of 5, while the System Usability Scale score was 79.61, falling into the acceptable category. The Yangyang model is designed to support document management, progress monitoring, rubric transparency, cross-semester archiving, and project publication through e-Showcase. However, the prototype still requires improvements in menu naming, button visibility, and guide search before the system is implemented.